Back Cover Image, Volume 1, Issue 2, April 2022. Issue 2 (22nd April 2022) - Unknown
Abstract : Back Cover : The operating temperatures of current LIBs (−20 60°C) cannot meet the demands of frigid zones and other extreme application fields. In article number 20210006, Chen et al. give a comprehensive overview of the promising strategies towards widetemperature applications in terms of solvent combination, lithium salts and film‐forming additives design.